On the Specificity of an Artistic Language: Plasticity and Space in Ben Nicolson’s Creative Work - Panova, Natalya G. (Actual Problems of Theory and History of Art, 2018)
The article is devoted to the works of Ben Nicholson, a 20th-century British artist, executed at different points in his career. Nicholson’s paintings, reliefs, and sculpture have been analyzed in the context of the development of European art in the 20th — early 21st century. An attempt has been made to consider the pictorial system of the artist from the point of view of its plastic, chromatic, and composite features. Certain parallels have been drawn with the works by other artists who influenced Nicholson’s creative method. The artist was a key figure in the development of Western abstract art. The article focuses on the formation of Nicholson’s special creative approach which expresses his philosophical outlook. The artist sought strict, logical, and organized forms. Ben Nicholson can safely be called an innovative artist and experimenter. His quest in the field of composition, color, shape, and painting technique resulted in an individual abstract style. As a result, the artist managed to create a coherent pictorial system — a set of various expressive means and methods, in which attention is paid to self-value of plane, line, rhythm, and perfection of texture. The combination of different expressive means and techniques in Ben Nicholson’s works has enriched the artistic language of our time.
Keywords: contemporary European art; abstract art painting; sculpture; artistic language; pictorial system; Ben Nicholson